Protease-nexin I as an androgen-dependent secretory product of the murine seminal vesicle. - Vassalli, J D (1993)
A search for inhibitors of urokinase-type plasminogen activator (uPA) in the male and female murine genital tracts revealed high levels of a uPA ligand in the seminal vesicle. This ligand is functionally, biochemically and immunologically indistinguishable from protease-nexin I (PN-I), a serpin ligand of thrombin and uPA previously detected only in mesenchymal cells and astrocytes. A survey of murine tissues indicates that PN-I mRNA is most abundant in seminal vesicles, where it represents 0.2-0.4% of the mRNAs. PN-I is synthesized in the epithelium of the seminal vesicle, as determined by in situ hybridization, and is secreted in the lumen of the gland. PN-I levels are much lower in immature animals, and strongly decreased upon castration. Testosterone treatment of castrated males rapidly restores PN-I mRNA levels, indicating that PN-I gene expression is under androgen control.